The Effect of Resistance Training on Menopausal Symptoms and Bone Health - Wrona, Julia; Kubiś, Natalia Marianna; Palacz, Bartosz; Teper, Maria Magdalena; Perz, Wiktor; Polus, Aleksander; Gluzicka, Anna; Olczyk, Liwia; Piotrowski, Jędrzej; Korolchuk, Anhelina (Quality in Sport, 2026)
Background: Menopause is a physiological stage undergoing a profound hormonal response to estrogen hormone changes which can profoundly impact skeletal health and overall health. Under estrogen deficiency, bone loss occurs more rapidly; individuals are prone to more osteoporosis and fractures; as well as, experiencing vasomotor complaints, such as hot flashes and night sweats. Resistance training has been recognized as an effective non-pharmacological method to counter these negative consequences. Aim: The aim of this review was to evaluate scientific evidence regarding the effects of resistance training on menopausal symptoms and bone health. Materials and Methods A search literature of medical and sports science literature was done in peer-reviewed publications in PubMed (MEDLINE), Web of Science, and Google Scholar. Randomized controlled trials, review articles, meta-analyses in scientific journals were incorporated. Outcomes The reviewed studies demonstrated that resistance training increases bone mineral density (BMD), particularly in the lumbar spine and femoral neck. More broadly, resistance training has shown to decrease the frequency and severity of vasomotor symptomatology in menopausal women. Conclusions: Resistance training improves bone health. It is important to recommend it as an adjunct to physical activity programs for menopausal women and as a minimum recommendation for this purpose as part of a large population of menopausal women.